Quality of Handroanthus serratifolius (Vahl) S. O. Grose seeds evaluated by the electrical conductivity test - da Cruz Silva, Patrícia; de Paula, Rinaldo; Valdovinos, Tamara; de Araújo, Márcio (Revista Ciência Agronômica, 2021)
The electrical conductivity test (EC) used to evaluate seed vigor is directly related to the integrity of cell membranes, but its use in forest species is still restricted. Thus, the objective of this study is to analyze the efficiency of the EC test to evaluate physiological parameters regarding seed quality and the genetic variability among Handroanthus serratifolius mother trees. Seeds from 15 mother trees were evaluated for germination (G%) and germination speed index (GSI). In the EC test, the seeds were imbibed in two water volumes (75 and 100 mL) at 20 and 25 °C, and the electrical conductivity was measured after five imbibition periods (24, 48, 72, 96, and 120 h). The germination test data were submitted to a randomized block design (RBD) analysis of variance and means were compared by the Scott-Knott test. The EC test was conducted as an RBD in a split-split plot scheme, with interaction unfolding by polynomial regression analysis. The mother trees were divided into four groups regarding G% and SGI. The EC test separated the mother trees into a larger number of groups, regardless of temperature, volume, and imbibition period. In conclusion, the EC test consisting of imbibition 25 seeds in 75 mL of deionized water at 20 °C for 48 h is suitable for evaluating the physiological quality of seeds and the variability among mother trees of Handroanthus serratifolius (Vahl) S. O. Grose.